Digital Transformation in Carbon Trading: Combination of Satellite and Blockchain Technology in REDD+ Schemes - Haryono, Haryono (West Science Agro, 2025)
Digitalization has introduced advanced technologies that can potentially revolutionize carbon trading systems, particularly in REDD+ programs. This study examines the application of satellite and blockchain technologies to enhance REDD+ programs. Satellite technology provides real-time, high-resolution forest imagery, ensuring accurate carbon stock measurement, while blockchain offers secure, transparent, and efficient carbon credit exchange platforms. With a combination of GIS analysis, literature review, and expert interviews, the study proposes an integrated framework that automates Monitoring, Reporting, and Verification (MRV) processes and prevents fraud in carbon trading. The findings indicate that combining these technologies can significantly enhance REDD+ credibility and scalability, but challenges such as high implementation costs, loopholes in regulations, and technical complexities must be addressed. This research maps the journey towards incorporating emerging digital technologies in climate change mitigation efforts.